2002
DOI: 10.1111/j.1945-5100.2002.tb00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Condensation processes in astrophysical environments: The composition and structure of cometary grains

Abstract: Abstract-We review the results ofour recent experimental studies ofastrophysical dust analogs. We discuss the condensation of amorphous silicates from mixed metal vapors, including evidence that such condensates form with metastable eutectic compositions. We consider the spectral evolution of amorphous magnesium silicate condensates as a function oftime and temperature. Magnesium silicate smokes anneal readily at temperatures of about 1000-1100 K. In contrast we find that iron silicates require much higher tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 42 publications
1
67
0
Order By: Relevance
“…Rietmeijer et al (1999) suggest that the observed growth occurs at metastable eutectic compositions and since MgO and FeO are completely miscible, there are no stable or metastable eutectic compositions along this axis of the phase diagram. This produces separate populations of magnesium silicate and iron silicate dust prior to aggregation and thermal processing of the aggregates (e.g., Nuth et al 2000Nuth et al , 2002. Formation of separate populations of magnesium silicate and iron silicate condensates from a mixed vapor may seem counterintuitive, but there is ample evidence to support this hypothesis in addition to the laboratory results cited above.…”
Section: Adding Iron and Magnesium To (Sio) N Nucleimentioning
confidence: 61%
“…Rietmeijer et al (1999) suggest that the observed growth occurs at metastable eutectic compositions and since MgO and FeO are completely miscible, there are no stable or metastable eutectic compositions along this axis of the phase diagram. This produces separate populations of magnesium silicate and iron silicate dust prior to aggregation and thermal processing of the aggregates (e.g., Nuth et al 2000Nuth et al , 2002. Formation of separate populations of magnesium silicate and iron silicate condensates from a mixed vapor may seem counterintuitive, but there is ample evidence to support this hypothesis in addition to the laboratory results cited above.…”
Section: Adding Iron and Magnesium To (Sio) N Nucleimentioning
confidence: 61%
“…Presently, a number of laboratories are conducting cosmic silicate and carbon dust analogues condensation experiments (e.g., Nuth et al, 2002;Fabian et al, 2000;Blanco et al, 1996) using similar but also different techniques than those reported in this paper. There are basically two different methods to generate the vapours in these experiments, viz.…”
Section: Introductionmentioning
confidence: 98%
“…Instead it will have a specific deep metastable eutectic composition. Most glass will be Mg-rich but there is no chemical constraint as DME dehydroxylate compositions can form in many chemical systems relevant to primitive dust compositions (Nuth et al 2000b(Nuth et al , 2002. I predict that when DME glass compositions in Stardust can be proven to be a recurring phenomenon, there is still a wealth of information on the smallest Wild 2 minerals hidden in these glasses.…”
Section: Discussionmentioning
confidence: 99%